2020
DOI: 10.1016/j.edurev.2019.100305
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status and academic performance in higher education: A systematic review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 87 publications
2
54
0
5
Order By: Relevance
“…Studies from a number of countries using various measures of social class origin and performance, consistently find an association between social origin and academic performance in higher education (Richardson et al., 2020; Rodriguez‐Hernandez et al., 2020; Smith & Naylor, 2001). Nothing indicates that law is an exception to these patterns.…”
Section: Social Origin and Academic Achievementmentioning
confidence: 99%
“…Studies from a number of countries using various measures of social class origin and performance, consistently find an association between social origin and academic performance in higher education (Richardson et al., 2020; Rodriguez‐Hernandez et al., 2020; Smith & Naylor, 2001). Nothing indicates that law is an exception to these patterns.…”
Section: Social Origin and Academic Achievementmentioning
confidence: 99%
“…The parental variables are indicators of educational level, occupational status and industry. As measures of the socioeconomic status of the student at the time of matriculation, the parental variables are potential vectors of academic performance (Delaney et al, 2011;Rodríguez-Hernández et al, 2020). Moreover, the relationship between personality traits and student scores may be influenced by parental characteristics as educational level and occupational industry.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Another line of research tackled students' educational or socioeconomic background. Students from lower socioeconomic backgrounds were found to have lower achievement (Rodríguez-Hernández, Cascallar, E., & Kyndt, 2020;Sirin, 2005). Several studies based on Social Capital Theory (Bourdieu, 1986) identified social capital as an explanation of how socioeconomic status is related to academic achievement.…”
Section: The Role Of Background Factorsmentioning
confidence: 99%
“…Several studies based on Social Capital Theory (Bourdieu, 1986) identified social capital as an explanation of how socioeconomic status is related to academic achievement. Yet, this idea was recently questioned and criticized (Rodríguez-Hernández et al, 2020). The meta-analysis of Richardson and colleagues (2012) estimated a corrected correlation of .15 with academic achievement.…”
Section: The Role Of Background Factorsmentioning
confidence: 99%